Effect of the manipulation of exercise order in the tri-set training system - Alex Silva Ribeiro; Danilo Rodrigues Pereira Silva; Matheus Amarante Nascimento; Ademar Avelar; Raphael Mendes Ritti-Dias; Edilson Serpeloni Cyrino (Universidade Federal de Santa Catarina, 2013)
The aim of this study was to analyze the effect of the manipulation of two different exercise orders using the tn-set system on the motor performance in exercises for the chest. Ten male (25.6 ± 5.7 years, 77.0 ± 5.8 kg, 172.9 ± 5.0 cm, 25.7 ± 1.4 kg/m2) with experience in resistance training underwent two experimental sessions, in which the subjects performed two sequences of exercises for the chest: SEQA (bench press, incline bench press, and peck deck) and SEQB (peck deck, incline bench press, and bench press). The load used allowed 8 to 12 repetitions (80% of 1RM) in each exercise. A higher number of repetitions (29 ± 2 reps vs. 26 ± 3 reps, P < 0.001) and a greater total overload (resistance used x repetitions performed = 1,942 ± 172 kg vs. 1,728 ± 234 kg, P < 0.001) were observed in SEQB. The results suggest that in the tn-set system the higher number of repetitions and a greater training volume occur when the single-joint exercise is included before multiple-joint exercises.